2017
DOI: 10.1080/13814788.2017.1401063
|View full text |Cite
|
Sign up to set email alerts
|

The new European guideline on cardiovascular disease prevention; how to make progress in general practice?

Abstract: The new guideline on cardiovascular disease (CVD) prevention, issued by the European Society of Cardiology was endorsed by 10 other societies, including Wonca Europe. It advices on how to reduce the cardiovascular (CV) risk in the population and attributes an important role to the general practitioner (GP). The GP is involved in treatment of the high-risk population as well as in public health measures to encourage a healthy lifestyle and CV risk factor reduction in the whole population. The new guideline give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Preventative behavior is an important aspect in the healthy functioning of the population [24]. In the author's own study there was no statistically significant difference between gender, financial situation, and the level of prophylaxis among the respondents.…”
Section: Discussionmentioning
confidence: 79%
“…Preventative behavior is an important aspect in the healthy functioning of the population [24]. In the author's own study there was no statistically significant difference between gender, financial situation, and the level of prophylaxis among the respondents.…”
Section: Discussionmentioning
confidence: 79%
“…These findings hold significant relevance within the context of new international cardiovascular prevention recommendations and future public health interventions aimed at their dissemination and implementation. Consequently, further studies are necessary to comprehend the factors associated with low compliance to CVD prevention interventions in the general population 27 . Three primary concepts pertaining to this issue merit attention: 1) Variations in clinical practice, which result in non-standardized healthcare and non-evidence-based clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study has identified a low rate of compliance with non-pharmacological interventions across all CVD risk categories. It is known that adherence to lifestyle changes in chronic conditions is poorer compared to pharmacological treatments (25) . Many of the rates reported in our study were similar to those documented in EUROASPIRE V for patients in secondary prevention (17) or exhibited a similar trend as the rates reported in the 2018 Argentina population-based survey of CVD risk factors (26) .…”
Section: European Action On Secondary and Primarymentioning
confidence: 99%
“…The need for improvement of cardiovascular disease (CVD) prevention is as important as ever [ 5 ], especially in primary care as most of these patients visit their family doctors (FD). Some of the major issues in primary care risk management are lack of time, limited number of educational tools, low patient motivation as well as adherence to the recommended treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%